Perancangan Model Bisnis Dengan Pendekatan Business Model Canvas Sebagai Strategi Pengembangan Bisnis pada Usaha Toko Online MFD Studio - Firza Khalisha Rinjany; Sinta Aryani; Nanang Suryana (Jurnal Ilmiah Wahana Pendidikan, 2022)
The growth of the fashion industry has become an opportunity for business actors, particularly small business owners, to develop their enterprises. MFD Studio is a women’s clothing online shop. Based on the available opportunities, MFD Studio has numerous chances to expand their business. However, MFD Studio faces a lot of rivals in the fashion business, which limits its ability to compete. Based on that condition, MFD Studio’s sales target is not achieved. This research aims to determine the business strategy through the business model canvas in order to increase sales. In this research, we identify MFD Studio's business model canvas existing, customer profile, and analyze the business model environment. After the data is collected, it is then processed using SWOT analysis. Based on the SWOT analysis, a business model strategy is obtained and then formulated into a proposed business model canvas. The results of this research are MFD Studio has to develop a strategy in the value.proposition, customer relationship, channels, cost structure, and revenue streams.